2017
DOI: 10.1186/s12966-017-0555-2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding differences between summer vs. school obesogenic behaviors of children: the structured days hypothesis

Abstract: BackgroundAlthough the scientific community has acknowledged modest improvements can be made to weight status and obesogenic behaviors (i.e., physical activity, sedentary/screen time, diet, and sleep) during the school year, studies suggests improvements are erased as elementary-age children are released to summer vacation. Emerging evidence shows children return to school after summer vacation displaying accelerated weight gain compared to the weight gained occurring during the school year. Understanding how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
486
4
55

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 580 publications
(584 citation statements)
references
References 184 publications
39
486
4
55
Order By: Relevance
“…This exploration study primarily focused on intrapersonal and interpersonal factors (ie, perceived competence, enjoyment, and peer support) but organizational and environmental factors such as the school structure and setting also play a key role in girls' PA behaviors . Similar to previous research, this exploration study found that girls are more active in school than out of school, providing support for the structure of the school day positively influencing PA behaviors …”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This exploration study primarily focused on intrapersonal and interpersonal factors (ie, perceived competence, enjoyment, and peer support) but organizational and environmental factors such as the school structure and setting also play a key role in girls' PA behaviors . Similar to previous research, this exploration study found that girls are more active in school than out of school, providing support for the structure of the school day positively influencing PA behaviors …”
Section: Discussionsupporting
confidence: 56%
“…Adolescent girls are more active during the school day compared to weekends and evenings . This is linked to the structured nature of the school day and numerous opportunities for PA (eg, physical education [PE] lessons and break‐times) . Thus , schools are a popular and accessible setting for PA promotion among adolescents.…”
mentioning
confidence: 99%
“…Based on these findings, it was concluded that it is not the type of programming, but rather mere engagement in structured programming that may lead to protection of weight gain 8. Importantly, these results align with the Structured Days Hypothesis9 which posits that exposure to a non-independent or structured environment (eg, week days during the school year) is beneficial to a child’s obesogenic behaviours and weight status. Also, results from this previous study8 corroborate with other similar studies demonstrating that routine participation in structured programming during the summer—summer school10 or summer programming11–15—may be beneficial to child weight status.…”
Section: Introductionsupporting
confidence: 73%
“…3,4 Evidence suggests that when children are out of school (eg, weekends and summer holidays), they are physically less active, have much longer screen time, irregular sleep patterns, and less favourable diets, resulting in weight gain and a loss of cardiorespiratory fitness. 3,4 Evidence suggests that when children are out of school (eg, weekends and summer holidays), they are physically less active, have much longer screen time, irregular sleep patterns, and less favourable diets, resulting in weight gain and a loss of cardiorespiratory fitness.…”
Section: Mitigate the Effects Of Home Confinement On Children Duringmentioning
confidence: 99%
“…Stressors such as prolonged duration, fears of infection, frustration and boredom, inadequate information, lack of in-person contact with classmates, friends, and teachers, lack of personal space at home, and family financial loss can have even more problematic and enduring effects on children and adolescents. 3 In the event of home confinement, parents are often the closest and best resource for children to seek help from. Furthermore, the interaction between lifestyle changes and psychosocial stress caused by home confinement could further aggravate the detrimental effects on child physical and mental health, which could cause a vicious circle.…”
Section: Mitigate the Effects Of Home Confinement On Children Duringmentioning
confidence: 99%